On the Relation of Conceptosphere and Mentality - Anvarovna, Fayziyeva Aziza (Researchparks Publishing, 2023)
The article examines a linguocultural concept that is useful for identifying the characteristics of a language community's worldview, and describes the approaches and classifications of the concept as a tool for the formation and interpretation of linguistic mentality.